Attitudes toward population and development issues among leaders in the Eastern Caribbean - Edenholm, Teresa L. (Caribbean Family Planning Association St John'sAG, 1986)
Analyzes views of 37 leaders in Caribbean society representing governments, churches, labour unions, medical officers, and women's organizations, on the impact of current population trends on the socio-economic development of the Eastern Caribbean. Considers knowledge of leaders on general demographic trends. Summarizes their views on adolescent fertility, status of women, and on family planning. Gives a country-by-country description of patterns in the responses of the individuals. Outlines recommendations of leaders on the preferred modes of dealing with identified population problems and discusses implications for the Caribbean Family Planning Association.